Sufi-Healing sebagai Model Terapi Penyakit Hati: Analisa Pemikiran Ibn Qayyim Al-Jauziyah - Jarman Arroisi; Achmad Reza Hutama Al Faruqi; Muhammad Basith (Spiritual Healing)
Sufi-healing aims to cleanse the heart from disease and at the same time enable a servant to carry out his worship in accordance with what Allah ordered to His Messenger. This article aims to reveal Sufi-healing according to Ibn Qayyim Al-Jauziyyah. In this research, the author used descriptive and analytical methods. After conducting in-depth research using literature studies, the author concluded that Ibn Qayyim explained that the right way to treat liver disease is one of them is by dhikr to Allah, by dhikr the heart will be clean. Once the heart is clean from inner trash and negative memories, the heart becomes more spacious, relieved and spacious. We can also feel inner peace. The impact of peace of mind is that we will feel happiness and avoid the diseases of greed, envy, envy, joy and so on. And in the end, our hearts will always feel calm and the focus will only be on worshiping and reciting remembrance of Allah SWT.